Synthesis of Calcium Phosphate by Microwave Hydrothermal Method - Ana Elisa Vilicev Italiano; Ricardo Luis Tranquilin; Danny Omar Mendoza Marin; Márcio Luiz dos Santos; Luís Geraldo Vaz (International Journal of Biomaterials)
Bone loss in the alveolar ridge is a factor widely studied by dentists in implant surgeries, as it poses a major challenge for aesthetic and functional recovery in patients with large maxillary bone defects. Synthetic biomaterials function as grafts designed to replace and remodel bone tissue. Calcium phosphate is a biomaterial that has good properties such as biocompatibility and bioactivity, making it a reference in bone replacement treatments. A synthetic biomaterial such as calcium phosphate can be obtained by various synthesis techniques. The microwave hydrothermal method (HTMO) is a pathway that allows changes in synthesis parameters and significantly increases the transmission efficiency of materials such as synthetic calcium phosphate derivatives. The study proposes obtaining a biomaterial for bone grafting based on calcium phosphate by the microwave HTMO and evaluating its microstructural and physicochemical characteristics. The parameters tested in this process were temperature and reaction time. The calcium phosphate particulates were obtained by the microwave HTMO at temperatures of 110°C and 130°C for 60 min and calcined at 300°C, 500°C, and 700°C. Microstructural and physicochemical characterization analyses were carried out using scanning electron microscopy, Fourier transform infrared, and X-ray diffraction. The results obtained showed the presence of more than one calcium phosphate biological interest phase, as hydroxyapatite (HA), tricalcium phosphate (β-TCP), and octacalcium phosphate (OCP), highlighting with increasing calcination temperature, the β-TCP phase becomes evident. The proposed synthesis method was efficient in obtaining a biomaterial with suitable physical and chemical characteristics, with an association of crystalline phases of biological interest related to the increase in synthesis temperature and calcination temperature.